1997
DOI: 10.1111/j.1471-0528.1997.tb11533.x
|View full text |Cite
|
Sign up to set email alerts
|

Third degree obstetric perineal tears: risk factors and the preventive role of mediolateral episiotomy

Abstract: Objective To determine risk factors for third degree obstetric perineal tears and to give recommendations for prevention.Design Retrospective case-control study.Setting A teaching hospital in The Netherlands.Participants and methods One hundred and twenty cases of vaginal delivery complicated by third degree perineal tear and 702 uncomplicated vaginal deliveries were compared, with respect to possible risk factors.Results In a multivariate model high birthweight, forceps delivery, induced labour, epidural anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
100
5
10

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(141 citation statements)
references
References 25 publications
26
100
5
10
Order By: Relevance
“…Severe laceration, such as a tear extending into the deep transverse perineal muscles and fibers of the anal sphincter (third degree) or rectal mucosa (fourth degree), is generally considered to occur with 5% of vaginal deliveries. 1 Some degree of perineal laceration, however, has been reported in up to 35% to 75% of all vaginal births. 2 A recent study found that 31% of female British obstetricians would choose cesarean delivery without any clinical indication because of concern about severe perineal damage.…”
mentioning
confidence: 99%
“…Severe laceration, such as a tear extending into the deep transverse perineal muscles and fibers of the anal sphincter (third degree) or rectal mucosa (fourth degree), is generally considered to occur with 5% of vaginal deliveries. 1 Some degree of perineal laceration, however, has been reported in up to 35% to 75% of all vaginal births. 2 A recent study found that 31% of female British obstetricians would choose cesarean delivery without any clinical indication because of concern about severe perineal damage.…”
mentioning
confidence: 99%
“…Poen et al had suggested that mediolateral episiotomy may be sphincter saving in nulliparous women. 3 Handa et al had documented likelihood of decreased 3 rd degree lacerations, but increased forth degree lacerations with episiotomy. 7 Birth weight was found to be statistically significant factor for development of obstetrical anal sphincter injuries.…”
Section: 7mentioning
confidence: 99%
“…[3][4][5] Rise in incidence is reported to be due to improved recognition of tears following implementation of standardised classification of tears.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, median episiotomy is associated with less blood loss and is easier to perform and repair than the mediolateral procedure [21]. However, median episiotomy is also associated with a higher risk of injury to the maternal anal sphincter and rectum than mediolateral episiotomies or spontaneous obstetric lacerations [22]. Mediolateral episiotomy is recommended for instrumental vaginal delivery [23].…”
Section: Episiotomymentioning
confidence: 99%